An Analysis of English Education Students’ Morphological Awareness (Morpheme Identification and Structure Awareness) - Henny Septia Utami; Mutiara Mujadidah (Journal of English Education and Teaching, 2021)
This study aims to describe English Education Students’ morpheme identification awareness, morpheme structure awareness, and overall morphological awareness. This research employed descriptive quantitative method. The samples of this research involved the whole sixth semester students of English Study Program IAIN Curup which consisted of 51 students who had taken morphology subject in previous semester.  The data were taken by giving the students a Morphological Awareness Test (MAT) which consists of Morpheme Identification Awareness test (MIAT) and Morpheme Structure Awareness test (MSAT). The results showed that the average score obtained in MIAT was 70,84 % in percentage, and the average score obtained in MSAT was 67,32 % in percentage. So, it can be concluded that both students’ morphological identification and structure awareness were in enough category. Then, students’ morphological awareness which was calculated from both MIAT and MSAT was also categorized as enough, 69,08% in percentage. From the overall average score, it was found that there were only 2 students who had very good morphological awareness. For good category, there were 18 students. Meanwhile, there were 19 students in enough category, and 12 students had low morphological awareness.